Integration of Traditional Sea Harvest Values in the Pancasila Student Profile Strengthening Project Through the Local Content Curriculum at Mayangan 2 Elementary School - Firmansyah, Firmansyah; Sabila El Maghfiroh Maromy (Elementaria: Journal of Educational Research, 2025)
This study aims to examine the integration of Petik Laut traditional values into local content curriculum and the Project for Strengthening the Pancasila Student Profile (P5) at SD Negeri Mayangan 2, Probolinggo City, and to analyze its impact on students’ character development. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with the principal, classroom teachers, local content teachers, and P5 facilitators, supported by participatory observation and document analysis. The data were analyzed thematically through data reduction, coding, categorization, and theme development, with validity ensured through triangulation and member checking. The findings reveal that the Petik Laut tradition embodies religious values, mutual cooperation, social responsibility, and environmental awareness, which align with the dimensions of the Pancasila Student Profile. The integration of these values into local content learning and P5 activities contributes positively to meaningful and contextual character internalization among students. However, the implementation remains gradual, highly dependent on teachers’ initiatives, and lacks systematic and sustainable learning modules. This study contributes by proposing a simultaneous integration model of local wisdom, the Merdeka Curriculum, and P5 as a strategic approach to strengthening character education in coastal elementary school contexts.